Effect of fungicidal contamination on survival, morphology, and cellular immunity of Apis mellifera (Hymenoptera: Apidae) - Kaur, Gurleen; Singh, Amandeep; Sharma, Rohit; Thakur, Abhinay; Tuteja, Shushant; Shyamli,; Singh, Randeep (Frontiers in Physiology, 2023)
Pesticide residues have been reported from hive stored products for a long time. Larvae of honey bees get oral or contact exposure to these products during their normal growth and development inside the cells. We analysed various toxicological, morphogenic and immunological effects of residue based concentrations of two fungicides, captan and difenoconazole on larvae of worker honey bees, Apis mellifera. Selected concentrations (viz, 0.08, 0.4, 2, 10 and 50 ppm) of both the fungicides were applied topically at a volume of 1 µl/larva/cell as single exposure and as multiple exposures. Our results revealed a continuous decrease in brood survival, in concentration dependent manner after 24 hours of treatment to capping and emergence stage. As compared to one time exposed larvae, multiply exposed youngest larvae were most sensitive to fungicidal toxicity. The larvae which survived higher concentrations showed several morphological defects at their adult stage especially under multiple exposures. Moreover, difenoconazole treated larvae showed significant decrease in number of granulocytes after 1 hour of treatment followed by an increase after 24 hours of treatment. Thus fungicidal contamination poses a great risk as tested concentrations showed adverse effects on survival, morphology and immunity of larval honey bees.